Demoralization narrative: Foul language of community figures - Munjiah, Ma’rifatul (Yayasan Irwan Abdullah Cendekia, 2023)
This study in addition to describing the speech-language in the communication process of community figures will also explain what the meaning behind the speech is. This study is descriptive and qualitative by using the netnography method. Data collection in this study was carried out through a reading process on 500 YouTube videos, using the search keywords